Effectiveness of Cognitive Behavioral Therapy on Mental Health and Suicidal Thoughts in Students - Rahimi, Bahare; Tavana, Sepideh; Heydari, Maryam; Khayati Ghasemkheily, Fatemeh Zahra; Ghasemi Kouchaksaraei, Ghazaleh (Health Nexus, 2023)
The current research aimed to determine the effectiveness of cognitive behavioral therapy (CBT) on mental health and suicidal thoughts among students. This semi-experimental study was conducted with a pre-test and post-test design. The population consisted of secondary school students in Tehran during the year 2022. Mental health and suicidal thoughts questionnaires were used in this study. The sample was selected using a convenience sampling method. Subsequently, 40 participants were divided into two groups: 20 in the experimental group and 20 in the control group. Both groups underwent a pre-test, followed by the experimental group receiving 90-minute CBT sessions weekly for 8 weeks, while the control group received no specific intervention. Afterward, a post-test was administered to both groups. The results of the data analysis using analysis of covariance indicated significant differences in mental health scores and suicidal thoughts in the post-test compared to the pre-test among participants in both the experimental and control groups. Therefore, cognitive behavioral therapy impacts mental health and suicidal thoughts in students.